Correlación entre los resultados arrojados en escalas Conners padres y escalas Conners maestros en niños manizaleños diagnosticados con TDAH - Giraldo Giraldo, Diana María (Universidad de San Buenaventura - Cali, 2017)
The aim of this study was to correlate the results obtained in the Conners Scale parents and teachers of children diagnosed with disorders Manizales attention deficit hyperactivity disorder, with the Colombian version adapted from the original scales in Spanish, (Pineda, 2000) for which the variables gender, age range, ADHD subtypes and socioeconomic strata of 89 children 5 to 15 years with ADHD were correlated. Data were analyzed using the coefficient of Pearson correlation and Student t test, and found moderate correlations in the variables: sex, age ranges, combined subtype and inattentive in the hyperactivity factor, and negative correlations in the factor of inattention in variables: age range, socioeconomic status, and combined subtype, parents rate greater inattention while more qualified teachers hyperactivity. I found relevant for future research where objectivity instruments considered.